If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5c+7=3c-5
We move all terms to the left:
5c+7-(3c-5)=0
We get rid of parentheses
5c-3c+5+7=0
We add all the numbers together, and all the variables
2c+12=0
We move all terms containing c to the left, all other terms to the right
2c=-12
c=-12/2
c=-6
| 3a+9=7a+5 | | 63+2x=105 | | 3(2x-3)=5(x+5) | | 2/3(y-18)=7 | | 7m=9+4m | | 63=2x=105 | | x-3/5=5 | | 2b+1=5b+10b= | | -9=-5-3a-11 | | a=15=4a-3 | | 7g-8=10g+8-4g | | -4(a+6)=-63 | | -6.5+1.3x=9.1 | | 3y+2=8y+17 | | h/2+h/3=6 | | 7r-8=6r | | 5(3x-8)=-115 | | 7r–8=6r | | 24-16x=72 | | 19u=8+18u | | 2y+6=3y+8y= | | 11b+3=-16+12b | | 4x+8=7.2+5x=0.8 | | 2y+6=3y+8,y= | | 14=-2+8x | | 4z+13=6z-17 | | 7.8b-2.14=-2.14=-42.7 | | 3y-35=139 | | 1/2(4x−6)+4x=27 | | -9-10m=-13 | | 3y-35=129 | | a+(-1.4)=-4.5 |